Mott Street : a Chinese American family's story of exclusion and homecoming - Chin, Ava (Penguin Press, an imprint of Penguin Random House LLC, 2023)
"Mott Street follows Chinese American writer Ava Chin, who grew up estranged from her father, as she seeks the truth about her family history--and uncovers a legacy of exclusion and resilience that speaks to the American experience past and present. Chin's ancestors became lovers, classmates, sworn enemies, and, eventually, through her birth, kin--all while converging at a single Chinatown address"--